(untitled) (Scientific journal of the Fergana State University, 2024)
My article, Amir Temur, a skilled strategist, is intended to promote our great history, the rich spiritual heritage of our great ancestors, and his contribution to the development of world civilization and military art among the youth of todayʼs young generation studying in educational institutions. and serves as a very important up-to-date information on patriotic education..